Personal health care companion – a medication assistant robot - Zawad, Farhan Sadick; Khan, Md. Sohel Aman; Farabi, Ahmed Rahman; Ankur, Md. Rafi Uddin; Rahaman, Touhidur (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016